Science and religion in India: Beyond disenchantment - Thomas, Renny (London Routledge, 2022)
This book provides an in-depth ethnographic study of science and religion in the context of South Asia, giving voice to Indian scientists and shedding valuable light on their engagement with religion. Drawing on biographical, autobiographical, historical, and ethnographic material, the volume focuses on scientists$1 (Breligious life and practices, and the variety of ways in which they express them.s